INDONESIA COMPLIANCE WITH HYOGO FRAMEWORK FOR ACTION (HFA) 2005-2015, AS THE GLOBAL FRAMEWORK ON DISASTER RISK REDUCTION - , DWI PRAMESWARI, Drs. Muhadi Sugiono, MA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The natural hazard is the unavoidable phenomenon, yet it is also unpredictable. Unfortunately, the natural hazard increases every year. The natural hazard supersedes into disaster due to the presence of vulnerability, unpreparedness, and unawareness, among the society. In addition, population grows along with conflicts, but the absence of solution remained. Indeed, those situations lift up the disaster risk evenmore. Therefore, recently the international community has been collaborating at the prospective framework, called Hyogo Framework for action, in order to raise countriesâ attention on overcoming those problem. They finally decide to react regarding on disaster risk reduction. It is coped all together in the global disaster risk governance through sharing the idea and information, setting up the minimum standard of disaster risk reduction efforts, and assisting countriesâ member to strengthening their local capacity on reducing the disaster risk. Those actions are able to take force due to the existence of globalization. It is very necessary that countries, especially with high disaster risk and vulnerability such Indonesia, are able to adopt and to adapt the framework in order to improve their disaster management system. Furthermore, Indonesia is well-known as the most vulnerable country with high disaster risk. Hence, this thesis would identify and analyze how Indonesia compliance with the framework, as well as its aim, building the resilience of nations and communities to disasters, in order to determine their efforts on reducing the disaster risk and pursue the resilience. However, Indonesia has demonstrated prospective progress on disaster risk reduction efforts through various policies, but the constraints still remain. Therefore, those constraints would be identied and analyzed comprehensively